1999
DOI: 10.1128/aem.65.1.311-314.1999
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthetic Pathway of Citrinin in the Filamentous Fungus Monascus ruber as Revealed by 13 C Nuclear Magnetic Resonance

Abstract: Carbon isotope distribution of [13C]citrinin fromMonascus ruber incubated with [13C]acetate revealed that the biosynthesis of the toxin originated from a tetraketide, instead of a pentaketide as has been shown forPenicillium and Aspergillus species. The production of polyketide red pigments and citrinin by M. ruber may therefore be regulated at the level of the tetraketide branch point.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
70
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(77 citation statements)
references
References 14 publications
0
70
0
4
Order By: Relevance
“…In this study, compared with the control, citrinin production showed a decrease of 45.0% while yellow, red, and orange pigment production showed an increase of 72.9, 73.9, and 40.1%, respectively, with 1.6 mT LF‐MF treatment. As described by Hajjaj et al [1999], LF‐MF treatment might affect the tetraketide branch point but not the synthesis process of the precursor. In addition, relative expression levels of pksPT, pigR, veA , and laeA significantly increased and those of citrinin synthesis genes ( pksCT and ctnA ) apparently decreased after exposure to 1.6 mT LF‐MF relative to the control.…”
Section: Discussionmentioning
confidence: 94%
“…In this study, compared with the control, citrinin production showed a decrease of 45.0% while yellow, red, and orange pigment production showed an increase of 72.9, 73.9, and 40.1%, respectively, with 1.6 mT LF‐MF treatment. As described by Hajjaj et al [1999], LF‐MF treatment might affect the tetraketide branch point but not the synthesis process of the precursor. In addition, relative expression levels of pksPT, pigR, veA , and laeA significantly increased and those of citrinin synthesis genes ( pksCT and ctnA ) apparently decreased after exposure to 1.6 mT LF‐MF relative to the control.…”
Section: Discussionmentioning
confidence: 94%
“…With further study on genetic differences, we may gain new insight on this issue (data not shown). Previous work (Hajjaj et al 1999) on biosynthetic pathways of citrinin and red pigment has concluded that both polyketides, synthesized through two branches, derived from the same precursor, tetraketide. However, there is little study on the association between these two branches during the process of growth and metabolism of Monascus spp.…”
Section: Discussionmentioning
confidence: 99%
“…The desire to decrease or eliminate the production of citrinin in RMR and Monascus ‐related products has led to the study of the biosynthetic pathway of citrinin. In 1999, the biosynthetic pathway of citrinin in M. ruber was proposed using 13 C nuclear magnetic resonance (Figure ) (Hajjaj and others ).…”
Section: Monascus Molecular Biology a New Breakthrough (From The Latmentioning
confidence: 99%